2020
DOI: 10.1021/acsomega.0c00073
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Neutral and Charged Nanodiamonds in Aqueous Media Confined between Gold Surfaces under Normal and Shear Loading

Abstract: The dynamics of cubo-octahedral nanodiamonds (NDs) with three different surface treatments and confined in aqueous environments between gold surfaces under shear and normal loading conditions have been characterized via molecular dynamics (MD) simulations. The treatments consisted of carboxyl (−COO–) or amino (−NH3 +) groups attached to the NDs, producing either negatively or positively charged NDs, respectively, and hydrogen-terminated surfaces producing neutral NDs. Simulations were performed in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…While at high pressure, nanoparticles indented into the slabs, and then plowed through the surface during sliding, leading to atomic-scale wear and higher friction coefficient. Su et al [22] studied the dynamics of surface-modified nanodiamonds confined between gold surfaces under shear and loading via NEMD. It revealed that the size of the surface functional group played a vital role to determine the slide or roll motion of nanodiamonds on solid contacts.…”
Section: Introductionmentioning
confidence: 99%
“…While at high pressure, nanoparticles indented into the slabs, and then plowed through the surface during sliding, leading to atomic-scale wear and higher friction coefficient. Su et al [22] studied the dynamics of surface-modified nanodiamonds confined between gold surfaces under shear and loading via NEMD. It revealed that the size of the surface functional group played a vital role to determine the slide or roll motion of nanodiamonds on solid contacts.…”
Section: Introductionmentioning
confidence: 99%
“…The authors, therefore, demonstrated how both surface functionalization and electrostatics contribute to determining the adhesive binding strengths (Figure 14). In a follow-up study, the same group modeled tribological contact between two gold surfaces lubricated with NDs in water to explore friction levels, rolling, and surface deformation [79]. Higher friction levels were notably observed when induced image charges in the gold contacts were present versus when they were absent.…”
Section: Interdependent Roles Of Electrostatics and Surface Functiona...mentioning
confidence: 99%
“…5.5. Probing Self-Assembly and Nonlinear Friction Behavior of Confined Gold Nanoparticles [33] In this nanotribological study, the authors employed a surface forces apparatus to In a follow-up study, the same group modeled tribological contact between two gold surfaces lubricated with NDs in water to explore friction levels, rolling, and surface deformation [79]. Higher friction levels were notably observed when induced image charges in the gold contacts were present versus when they were absent.…”
Section: Potential-controlled Boundary Lubrication Using Mos2 Additiv...mentioning
confidence: 99%
“…It should be pointed out that all these above-mentioned simulations with sliding walls are nonequilibrium molecular dynamics (NEMD) simulations in tribology [28]. According to previous studies [29][30][31][32][33][34][35], there is no doubt that NEMD simulations provide unique insights into understanding the nanoscale friction and lubrication mechanisms. For example, Lee et al [29] studied the rolling resistance of a rigid Ni sphere of Cu substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Their simulation results revealed that the movement pattern turned into rolling from sliding when the nanoparticles were closer to a sphere. Su et al [35] mixed water and nanodiamonds that had charges as lubricant confined by two gold surfaces. They claimed that the nanodiamonds with negative charges dramatically increased friction force due to the combination of rolling and cutting movement patterns.…”
Section: Introductionmentioning
confidence: 99%